Potential of Producing Green Hydrogen Using Solar Power Plants: The Role of PEM Technology in the Improvement of Photovoltaic Schedule Keeping in Hungary - Gábor Pintér; Virag Meszaros; Nóra Hegedusné Baranyai; András Vincze; Henrik Zsiboracs (Chemical Engineering Transactions)
Similarly to many countries of the world, photovoltaic systems play an increasingly important role in electricity generation in Hungary, contributing greatly to the climate, environmental and sustainability goals of the energy transition. As a result of numerous factors, photovoltaic technology is used not only more and more widely but also in increasingly decisive quantities and proportions. Due to the intermittent nature of solar energy, photovoltaic generation varies both in space and over time and consequently poses a serious challenge to system management, especially due to dynamically developing capacities. The imbalances caused by uncertainty cannot be addressed by scheduling alone without the possibility of energy storage, which, with its numerous services and applications, is able to provide the flexibility necessary for the smooth operation of the system. Among the available energy storage systems, power-to-gas technology (i.e. converting electricity produced from renewable energy sources into a gaseous energy carrier) is emerging as a practical solution with high potential for the integration of variable renewable energy sources. The gas produced in this way, which can be stored and transported, can be used in many areas and sectors of energy use, such as transport, home heating and cooling and industrial processes, and can now also provide an effective solution for grid stability and scheduling. The aim of the present research is to present the potential amount of green hydrogen that can be produced by proton-exchange membrane technology (PEM) in connection with schedule-related downregulation, considering the climatic conditions and the total photovoltaic power plant capacity in Hungary. The novel, practical benefit of the research lies in the fact that it determines practically relevant characteristics in relation to the interconnections of solar power plants in Hungary and power-to-gas technology for transmission system operators, the key players of the energy market and decision-makers. This knowledge will not only help companies investing in solar power plants and power-to-gas technology from an economic point of view but can also contribute to the market-related development of hydrogen production solutions related to photovoltaic technology. Overall, P2G offers the ideal potential to convert the electricity produced by solar power plants that need to be downregulated, i.e. comprises a surplus in terms of scheduling, into green hydrogen, which is also suitable for long-term seasonal storage.